Pengaruh Komitmen Afektif, Stres Kerja, Work Engagement Terhadap Turnover Intention Perawat - Muchtadin, Muchtadin; Sundary, Zevy Emmelya (Journal of Health Management Research, 2023)
Background: Nurse turnover intention is important because it can increase costs for recruiting non-permanent nurses, reduce nurse performance and productivity, reduce organizational performance.Aims: This study seeks to determine the extent of affective commitment, work stress, work engagement on turnover intention of Bakti Timah Medika Pangkalpinang nurses.Methods: This study uses a descriptive quantitative design. Sampling used a saturated sample but 91 out of 212 nurses who were willing to be respondents. The data analysis used is PLS-SEM and processed with Smartpls.Results: The results of the study found that affective commitment had a significant negative impact on turnover intention. Work stress has a significant positive impact on turnover intention. Work engagement has no impact on nurse turnover intention. Conclusion: The level of nurse turnover depends on affective commitment and work stress factors. Future researchers can use connectors such as affective commitment and work stress on the effect of work engagement on turnover intention. Hospital management should pay more attention to the affective commitment and work stress of nurses because it can reduce the intention to change job.